Tradisi Kerjasama Ma Agheh Dalam Hukum Ekonomi Syariah Di Masyarakat Padang Sago - Windra Firdaus; Edriagus Saputra (Institut Agama Islam Sumatera Barat, 2023)
This research aims to reveal the tradition of ma agheh cooperation implemented by the Padang Sago community. This article discusses the history and laws related to the implementation of the ma agheh tradition in the process of land and crop management cooperation. The research is a field study using qualitative methods. The results of this study can be concluded, that this tradition is a community custom that has been carried out for generations by the local community. Based on Sharia Economic Law, the implementation of this tradition does not violate Sharia law because this cooperation has been agreed upon by both parties, both the landowner and the manager and this is a form of 'urf. In addition, the ma agheh tradition needs to adjust the existing urf with the principles of Sharia Economic Law.